Entry deterrence when the potential entrant is your competitor in a different market - Ropero-García, Miguel Ángel (Wiley Online Library, 2021)
In this article, we present a two-period model in which one firm operates in two markets: a monopoly and a duopoly. Assuming that this firm has private information on the cross-price elasticity of demand between the products sold in both markets, it limits its quantity supplied in the monopoly market in order to make its rival in the other market believe that entry into the monopolized market is unprofitable. As a result of this strategy, the average prices observed in both markets increase. This result suggests that the detrimental effects of entry deterrence on consumers´ welfare are stronger than those predicted by previous literature.
Keywords: Monopolios; Competencia económica; Entry deterrence; Pooling equilibrium; Separating equilibrium; Signalling game; Undefeated equilibrium